The Influence of Handgrip and Motor Exercise on Ability to Play Table Tennis - Puspita, Netty; Lian, Bukman; Akhbar, M Taheri (Journal of Social Work and Science Education, 2023)
This study aims to determine motor handgrip exercises on the ability to play table tennis either partially or simultaneously. The population and sample in this study were 104 students at Elementary School 5 of Rambang. The method used in this study is a quantitative method. The data collection techniques used observation and test techniques. The data analysis technique uses parametric statistical tests with the t-test formula. The results of this study concluded that: (1) There is a partial effect of handgrip training on the ability to play table tennis. The results of the analysis of the coefficient of determination of the first hypothesis test partially obtained t-count 3.897 > t-table 1.987; (2) There is a motoric effect on the ability to play table tennis. The results of the analysis of the coefficient of determination of the second hypothesis test obtained t-count 3.839 > t-table 1.810; (3) There is a simultaneous effect of handgrip and motoric exercises on the ability to play table tennis. The results of the analysis of the coefficient of determination of the third hypothesis test obtained F-count > F-table or 13.587 > 0.967.